A phase II study of cisplatin plus S-1 with concurrent thoracic radiotherapy for locally advanced non-small-cell lung cancer: The Okayama Lung Cancer Study Group Trial 0501. Issue 2 (February 2015) - Nogami, Naoyuki; Takigawa, Nagio; Hotta, Katsuyuki; Segawa, Yoshihiko; Kato, Yuka; Kozuki, Toshiyuki; Oze, Isao; Kishino, Daizo; Aoe, Keisuke; Ueoka, Hiroshi; Kuyama, Shoichi; Harita, Shingo; et al.
Highlights: A S-1-based chemo-radiation was effective and safe in stage III NSCLC. The median progression-free survival time was 9.3 months. The median survival time was 31.3 months. Toxicities were generally mild except for febrile neutropenia and pneumonitis. Abstract: Background: Although cisplatin-based chemotherapy combined with thoracic irradiation (TRT) is a standard treatment for unresectable, locally advanced non-small cell lung cancer (NSCLC), this treatment outcome has remained unsatisfactory. We had previously conducted a phase I trial of cisplatin plus S-1, an oral 5-fluorouracil derivative, and TRT, which were safe and effective. Methods: In this phase II trial, 48 patients with stage III NSCLC received cisplatin (40 mg/m 2 on days 1, 8, 29 and 36) and S-1 (80 mg/m 2 on days 1–14 and 29–42) and TRT (60 Gy). The primary endpoint was the response rate. Results: A partial response was observed in 37 patients (77%; 95% confidence interval: 63–88%). At a median follow up of 54 months, the median progression-free survival and median survival time were 9.3 and 31.3 months, respectively. No difference in efficacy was observed when the patients were stratified by histology. Toxicities were generally mild except for grade 3 or worse febrile neutropenia and pneumonitis of 8% and 4%, respectively. No patient developed severe esophagitis. At the time of this analysis, 35 (73%) of the 48 patients recurred; 15 (31%) showed distant metastasis, 17 (35%) had loco-regional disease, and 2 (4%) showed both loco-regional disease and distant metastasis. Conclusions: This chemoradiotherapy regimen yielded a relatively favorable efficacy with mild toxicities in patients with locally advanced NSCLC.